Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Tamu Gardenia Cafe Shop di Sintesa Peninsula Hotel Manado - Wijanarko, Sonny; Gosal, Meily E. (Jurnal Hospitaliti, 2024)
This research aims to find out and analyze the influence of service quality and facilities on guest satisfaction at the Gardenia Café Shop at Sintesa Peninsula Hotel Manado. The research method used iQuantitative Method, with techniques resulting from Multiple Linear Regression Analysis. The population in this study were hotel guests, with sample of 30 guests at Sintesa Peninsula Hotel Manado. Data was collected by distributing questionnaires using a Likert scale, using the SPSS version 26 application. Based on the results of calculations and tests, it was found that the service quality variable had a positive and significant effect on guest satisfaction with tcount 1.210 > ttable 2.052, the facility variable had a positive and significant effect on guest satisfaction with tcount 4.749 > ttable 2.052, the service quality and facilities variables had a simultaneous effect on guest satisfaction with Fcount 42.386. The next test results based on the Coefficient of Determination showed the partial influence of service quality and facilities on guest satisfaction with a regression result of 0.758 or 75.8%.